2020
DOI: 10.1021/acs.energyfuels.9b04091
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of NOx-Reduction Measures for Iron-Ore Rotary Kilns

Abstract: The grate-kiln process is employed for sintering and oxidation of iron-ore pellets. In this process, a fuel (typically coal) is combusted with a large amount of excess air in a rotary kiln, and the high air-to-fuel ratio leads to significant NO x formation. The current Article is an assessment of NO x reduction measures that have been tested in pilot-scale and in full-scale by the Swedish iron-ore company Luossavaara-Kiirunavaara Aktiebolag (LKAB). The results show that the scaling between the full-scale kiln … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Rotary kilns are long cylindrical furnaces used for the production of cement and other material processing applications [1]. These furnaces have been studied extensively both numerically [2][3][4] and experimentally [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Rotary kilns are long cylindrical furnaces used for the production of cement and other material processing applications [1]. These furnaces have been studied extensively both numerically [2][3][4] and experimentally [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…These include the design of low NOx swirl burners, catalytic reduction techniques and systems that enrich the oxidizer with oxygen. A recent overview for iron-ore rotary kilns is given in [7]. The numerical simulation is deemed to be vital to render these counter measures even more effective.…”
Section: Introductionmentioning
confidence: 99%
“…While studies, such as in [20], have shown that for diffusion flames it may increase with leaner mixtures (constant adiabatic temperature and more oxygen available). Moreover, since the actually operating kiln is burning natural gas which contains nitrogen, fuel NOx may form with excess air, as what occurs with coal combustion shown in [22,23]. However, we are aware that many factors play a role that leads to this behaviour that we see in the measurements.…”
Section: Preliminary Nox Validationmentioning
confidence: 84%
“…There are some studies applied to rotary kilns where, partially, the influence of the AFR on NOx formation is investigated. In [22], both experimental and numerical works (using a chemical reactor model) are done on a small pilot scale and full scale kiln. In [23] experimental work is conducted on the precalciner whereas the kiln is experimentally simulated.…”
Section: Introductionmentioning
confidence: 99%